2020
DOI: 10.15419/bmrat.v7i9.626
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P16 biomarker in squamous cell carcinoma of uterine cervix and its association with clinico-pathological parameters: A cross-sectional study

Abstract: Introduction: Cervical cancer is the most common cancer among females. P16 is the surrogate marker for cervical carcinoma. This study aimed to evaluate the association of P16 marker with clinic-pathological parameters in squamous cell carcinoma of uterine cervix. Methods: This was a cross-sectional study. Histological confirmed cases of squamous cell carcinoma (SCC) of cervix were considered. All cases were evaluated for IHC P16 expression as per lower anogenital squamous terminology (LAST) criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…In the present study, IHC P16 expression in terms of diffuse block positive, focal nuclear positive or negative expression showed block positivity in 22 cases (44.0 %), focal nuclear in 18 cases (36.0%) and negativity in 10 cases (20.0 %); with overall 80% p16 positive and 20% p16 negative. Our results agreed with Sarwath et al [15] and Kaylani et al [16] trials, where anti-p16 ink4a IHC correlation in SCC and other cervical tumors showed positive expression in 92% and 89% respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, IHC P16 expression in terms of diffuse block positive, focal nuclear positive or negative expression showed block positivity in 22 cases (44.0 %), focal nuclear in 18 cases (36.0%) and negativity in 10 cases (20.0 %); with overall 80% p16 positive and 20% p16 negative. Our results agreed with Sarwath et al [15] and Kaylani et al [16] trials, where anti-p16 ink4a IHC correlation in SCC and other cervical tumors showed positive expression in 92% and 89% respectively.…”
Section: Discussionsupporting
confidence: 93%